2009
DOI: 10.1161/circulationaha.108.843169
|View full text |Cite
|
Sign up to set email alerts
|

Donor Pretreatment With Hypertonic Saline Attenuates Primary Allograft Dysfunction

Abstract: Background-Hypertonic saline (HTS) has been previously demonstrated to have immune modulatory and vascular protective effects. We assessed the effect of donor pretreatment with HTS on allograft preservation in a porcine model of orthotopic heart transplantation. Methods and Results-Orthotopic transplants were performed after 6 hours of cold static allograft storage. Donor pigs were randomly assigned to pretreatment with (nϭ7) or without (nϭ6) HTS (4.5 mL/kg of 7.5% NaCl) administered 1 hour before donor heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
1
14
0
6
Order By: Relevance
“…1 As they note, we observed enhanced ventricular recovery in addition to preserved coronary artery vasomotor function with donor pretreatment with hypertonic saline in a porcine heart transplant model. They postulate that a mechanism to explain our positive results is the prevention of intracellular Ca 2ϩ accumulation induced by extracellular hypernatremia.…”
supporting
confidence: 56%
“…1 As they note, we observed enhanced ventricular recovery in addition to preserved coronary artery vasomotor function with donor pretreatment with hypertonic saline in a porcine heart transplant model. They postulate that a mechanism to explain our positive results is the prevention of intracellular Ca 2ϩ accumulation induced by extracellular hypernatremia.…”
supporting
confidence: 56%
“…In fact, high sodium levels have been suggested to be beneficial for the heart after short-term global ischaemia. It was shown that in a porcine model of orthotopic heart transplantation, hypertonic saline treatment attenuates posttransplantation cardiac allograft dysfunction and improves haemodynamics [13]. Infusion of 7.5% NaCl in a clinically relevant dose causes only minor changes in the acid-base balance in normovolaemic women [14].…”
Section: Discussionmentioning
confidence: 99%
“…M. Badiwalla и соавт. получили данные о том, что в модели у свиней при ортотопической трансплантации сердца, использование ГР у донора непосредственно перед забо ром аллографта и его хранением, ограничивает эндотелиальное повреждение и улучшает восстановление сердечной деятельнос ти после трансплантации [52]. Одним из наиболее частых осложнений операций в ус ловиях ИК является повреждение головного мозга [53].…”
Section: о б з о р ыunclassified